Human papillomavirus vaccine uptake and its determinants among women in Africa: an umbrella review - Mengistie, Berihun Agegn; Yirsaw, Amlaku Nigusie; Lakew, Gebeyehu; Mekonnen, Gebrehiwot Berie; Shibabaw, Adamu Ambachew; Chereka, Alex Ayenew; Kitil, Gemeda Wakgari; Wondie, Wubet Tazeb; Abuhay, Alemken Eyayu; Getachew, Eyob (Frontiers in Public Health, 2025)
BackgroundGlobally, cervical cancer is the fourth most prevalent disease among women. It is primarily caused by persistent infections with human papillomavirus (HPV). The World Health Organization (WHO) strongly recommends HPV vaccination for girls aged 9 to 14 years. Although HPV vaccination is the most effective form of primary prevention against cervical cancer, the accessibility and uptake of the HPV vaccine remain low in developing nations, particularly in Africa. Therefore, this umbrella review aimed to determine the pooled prevalence of human papillomavirus vaccine uptake and its determinant factors in Africa.MethodsThe protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) under reference number CRD42024560032. Eligible systematic review and meta-analysis (SRM) studies were retrieved from PubMed, Hinari, ScienceDirect, and Google Scholar. Data were extracted using Microsoft Excel 2019 and analyzed using Stata software (version 17). The methodological quality of the included studies was examined using A Measurement Tool to Assess systematic Reviews (AMSTAR 2). Publication bias was checked using a funnel plot and Egger’s test. A random-effects model (DerSimonian–Laird method) was used to estimate the pooled prevalence of HPV vaccine uptake. The I-squared (I2) test was performed to assess statistical heterogeneity among the included studies.ResultsThis umbrella review included five SRM studies conducted across Africa, encompassing a total of 707,005 study participants. The pooled prevalence of HPV vaccine uptake in Africa was 41.38% (95% CI: 34.70, 48.06). Women’s knowledge of HPV vaccination (AOR: 3.22, 95% CI: 1.64–6.33) and attitudes toward HPV immunization (AOR: 2.48, 95% CI: 2.18–2.81) were significantly associated with HPV vaccine uptake.ConclusionThe uptake of the HPV vaccine in Africa remains significantly lower (41.38%) than the WHO’s global HPV vaccination target of 90% by 2030. Therefore, increasing vaccine uptake requires promoting women’s knowledge and attitudes toward HPV vaccination through facility-based education and counseling, planned campaigns, community-based programs, and advocacy for HPV vaccination and cervical cancer prevention using various mass media platforms.Systematic review registrationBerihun Agegn Mengistie, Muluken Demeke, Abebaw Setegn. An Umbrella review of Human Papillomavirus (HPV) Vaccine Uptake and its predictors among females in Africa, 2024. PROSPERO 2024 Available from https://www.crd.york.ac.uk/PROSPERO/view/CRD42024560032.